Spectrum-like graphical representation of DNA based on codons - Randić, Milan (Acta chimica slovenica, 2006)
We consider a novel 1-Dimensional representation of DNA, which is based on graphical representations of the 64 triplets of nucleic acids on the peripheryof the unit circle. By using the polar coordinate of 64 codons (expressed in radians) four letter DNA sequence is transformed into a numerical sequence with no more than 64 different entries. By depicting the 1-Dim representation (plotted on z-coordinate) and using the x co-ordinate as running index one obtains Ćspectrum-likeĆ graphical representation of DNA. The novel representation of DNA has some advantages over other spectrum-like 1- dimensional and 2-dimensional representations in using the same coordinatesfor the same codons thus avoiding computations of coordinates, which is characteristic of the Jeffreyćs algorithm and graphical representations of DNA based on its modification
Keywords: DNA; računalniška kemija; reprezentacija; struktura